PROGRESSIVISM OF JUDGES IN DECIDING APPLICATIONS FOR MARRIAGE DISPENSATION - Josua Navirio Pardede; Wigati Taberi Asih; Thogu Ahmad Siregar (Lambung Mangkurat Law Journal, 2021)
Regulation on the age limit for a marriage through Act No. 16 of 2019 is based on the spirit of anti-discrimination and protection of children’s rights from the adverse effects of child marriage. However, the efforts to complicate and prevent child marriage has yet to have a significant impact on reducing the rate of child marriage in Indonesia. This condition is occurred by the high level of applications for marriage dispensation that are granted by the court. Hence, the construction of the judge’s reasoning in observe the relationship between the substance of the law and the reasons for proposing marriage dispensation is one of the most vital and influential elements. The positivism-legism legal reasoning used in understanding of Act No.16 of 2019 is considered to be the cause of the malfunction of the regulation in protecting and guaranteeing children’s human rights. By using doctrinal legal research methods, this research produces a conceptual analysis in the form of a meta-juridical critique on positivist legal reasoning which tends to lead to the legism when trying to understand the objectives of Act No. 16 of 2019 and proposes a progressive legal notion as an ideal reasoning framework in producing decisions on applications for dispensation of marriage that have a perspective on the protection and guarantee of children’s rights.